2022
DOI: 10.3390/agriculture12060794
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Impacts of Climate Change on Maize Yields Using EPIC: A Case Study in the Eastern Cape Province of South Africa

Abstract: Climate change has been projected to impact negatively on African agricultural systems. However, there is still an insufficient understanding of the possible effects of climate change on crop yields in Africa. In this study, a previously calibrated Environmental Policy Integrated Climate (EPIC) model was used to assess the effects of future climate change on maize (Zea mays L.) yield in the Eastern Cape Province of South Africa. The study aimed to compare maize yields obtained from EPIC simulations using basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Different crop modeling have predicted that maize production will decrease by 14-17 % by 2041-2060, and sowing date and cultivar types are significant factors in mitigating climate change (10). Another study forecasted that maize production will decrease by 23.8% and temperature in the winter season will rise by 50 % as per the projection of a model (Environmental Policy Integrated Climate or EPIC) for the period 2070-2099 (14). As per the studies, the impact of climate change can be reduced considerably by proper agronomic management practices such as delaying sowing dates, and developing new germplasms through molecular plant breeding.…”
Section: Effect Of Temperature On Growth and Yield Parameters Of Maizementioning
confidence: 99%
“…Different crop modeling have predicted that maize production will decrease by 14-17 % by 2041-2060, and sowing date and cultivar types are significant factors in mitigating climate change (10). Another study forecasted that maize production will decrease by 23.8% and temperature in the winter season will rise by 50 % as per the projection of a model (Environmental Policy Integrated Climate or EPIC) for the period 2070-2099 (14). As per the studies, the impact of climate change can be reduced considerably by proper agronomic management practices such as delaying sowing dates, and developing new germplasms through molecular plant breeding.…”
Section: Effect Of Temperature On Growth and Yield Parameters Of Maizementioning
confidence: 99%
“…Severe droughts in South Africa have led to water scarcity and reduced agricultural productivity. In recent years, the country has experienced drought-related losses in key sectors like maize production and livestock farming 112 . India, with its large agricultural sector, is highly vulnerable to drought.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature review, six main factors for the impacts of climate change on agriculture were identified: (i) Drought, floods, and food security [2,6,15,18,[22][23][24][25][26][27][28][29][30][31][32]; (ii) Temperature increases, changes in precipitation patterns [12,14,18,20,24,25,27,33,34]; (iii) Extreme weather events [7,24,35]; (iv) Occurrence of pests and diseases in plantations [2,6,35]; (v) Water and energy insecurity [2,36].…”
Section: Impact Of Climate Change On Agriculturementioning
confidence: 99%
“…These two climate variables have a significant effect on crops and their yield. Although rainfall affects agricultural production in terms of photosynthesis and leaf area, temperature affects the length of the growing season [7,10,20,[22][23][24][25][27][28][29][30][31][32]34,[36][37][38][39][40][41][42][43][44][45]. It is important to highlight other indicators, which were found in some articles, such as (i) drought 7.9% (5/63), (ii) humidity 1.5% (1/63), (iii) evaporation 1.5% (1/63) [12], as consequences of temperature and precipitation.…”
Section: Impact Of Variable Climate On Crop Yieldsmentioning
confidence: 99%
See 1 more Smart Citation